Polyaniline/MoSX supercapacitor by electrodeposition - Wang, Yong (2019)
Supercapacitors as a promising energy storage device have received significant attention. Here we report a facile, low cost and mass production strategy to prepare polyaniline (PANI)/ molybdenum sulfide (MoSX) supercapacitor material by electrodeposition. More specifically, PANI was electrodeposited on glassy carbon (GC) through chrono amperometry followed by electrodeposition of MoSX via chrono potentiometry from ammonium tetrathiomolybdate ((NH4)2MoS4) precursor. This composite material was characterized by X-ray photoelectron spectrum, scanning electron microscopy and energy-dispersive X-ray spectroscopy. In addition, PANI/MoSX shows superior capacitance of 48.64 mF cm¹2 at a current density of 56.62¯A cm¹2 and long-term stability without any degradation during the 150 cycles. The enhanced capacitance observed is from the combination of electrochemical behaviors of PANI and MoSX.